Utilization Arabica Skin Waste of Coffee as a Basic Material for Making Bioethanol in Sukorejo Village, Sumber Wringin District Bondowoso Regency - Gatot Subroto; Djoko Soejono (Warta Pengabdian, 2022)
Sukorejo Village is a village located in Sumber Wringin District, Bondowoso Regency. Most of the residents work as agricultural laborers in the PTPN XII Plantation and a partial small as owners of the Arabica coffee plantations. The potential Arabica coffee waste belonging to the people, both solid waste and liquid waste, in each stage of the processing process is very large, but so far it is still very little used. Usually the coffee skin waste is only allowed to accumulate in the processing plant, causing an unpleasant odor and polluting the surrounding environment. The waste generated from the process of separating coffee skins from coffee beans (pulping process) in the form of biomass is very abundant, and few percent used for livestock feed and compost. One farmer group during the coffee harvest season (about 4 months) requires premium fuel of approximately 2 liters per day for the process of grinding coffee cherries into coffee powder. The waste generated from the process of separating coffee skins from coffee beans in the form of biomass is very abundant, and is only used a few percent for animal feed and compost. Therefore, to overcome the need for fuel, namely by utilizing coffee husk waste as a basic material for making bioethanol. Taking into account the above conditions, this service is carried out in Sukorejo Village, Sumber Wringin District, Bondowoso Regency, with the hope of increasing farmers' income by reducing the cost of purchasing fuel.